Inheritance of Earliness and Bulb Weight in the Common Onion (Allium cepa L.) - EL-SHAFIE, M. W.; AHMED, A. A. (The Libyan Journal of Agriculture, 2023)
The objective of the present study was to investigate the genetic behaviour of two characters in onions (Allium cepa L.), namely, earliness and bulb weight. Two crosses were made, the first involved the Egyptian cultivars Behairy and Giza 6 Mohassan and the second was between two local inbred lines L 1421 and L324. Behairy and L1421 were late in maturity, whereas L 324 was early. Giza 6 Mohassan cultivar was characterized by moderate earliness. With respect to bulb weight, Behairy and L 324 parents showed higher bulb weight than Giza 6 Mohassan and L 1421 parents. Parents, F, and F2were , grown and measurements were recorded. Data were then genetically and statistically analysed. The F2 distributions of the first and second cross indicated partial dominance of lateness over earliness. F2 distributions of both crosses showed some skewness toward < lateness but it was significant only in the second cross. It was difficult to draw a certain conclusion concerning the action of genes involved in the inheritance of this character. However, F, results of the first cross indicated multiplicative gene action. The results suggested the presence of more than one pair of genes controlling the character. Herit-ability values ranged from 37.8 to 52.75%. Based on 5% selection intensity, the F3 mean would be expected to be shifted 4.95-5.47% earlier than the F2 means in the firstand second cross, respectively. Small bulb weight was overdominant to larger bulb weight. F2 distributions of both crosses showed positive and highly sinificant skewness. The determination of gene action was difficult in the first cross, but the second cross indicated additive gene action. w At least one pair of major genes was found to control the parental differences in bulb weight. High to moderate heritability values were obtained, 77.77 and 48.53% for the first and second cross respectively. Based on 5% selection intensity, the expected genetic gain in F3 ranged from 50.19-80.35% of the F2 means for the second and first cross, respectively.